Fractional CO2 Laser in the Treatment of Post-Menopausal Vaginal Atrophy Fractional CO2 Laser in Post-Menopausal Women (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: vaginal atrophy; vaginal rejuvenation; fractional CO2 laser